Sources of value creation in acquisitions: An empirical investigation - Seth, Anju (Strategic Management Journal, 1990)
Abstract This study provides a conceptual framework and an empirical methodology to assess the relative importance of different sources of value creation in acquisitions. The empirical results indicate that value creation in related acquisitions is associated with economic efficiencies hypothesized to arise both from economies of scale and scope and from operating efficiencies, and with market power. In unrelated acquisition, where such efficiencies are not expected to be present, value creation occurs nevertheless and is associated with the coinsurance effect. Finally, it is shown that financial diversification effects do not play a role in value creation in either type of acquisition.